Preserving Cultural Heritage Through Traditional Institutions and Youth Engagement: Melestarikan Warisan Budaya Melalui Lembaga Tradisional dan Partisipasi Pemuda - Agustina Lirim; Muhammad Habibi; Trisna Waty Riza Eryani; Prawira Yudha Pratama (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Cultural preservation is a pressing issue in Indonesia, where traditional heritage faces erosion due to modernization and shifting values. Specific Background: Lung Anai Cultural Village in East Kalimantan, home to the Dayak Kenyah Lepoq Jalan community, embodies rich traditions such as traditional dance, weaving, carving, and ceremonies, yet these practices are declining, particularly among youth. Knowledge Gap: While traditional institutions are recognized for safeguarding culture, limited empirical research examines their operational roles, youth engagement, and contextual challenges at the village level. Aims: This study analyzes the role of the Lung Anai Traditional Institution in preserving cultural heritage, identifying its functions, supporting factors, and obstacles. Results: Using a qualitative descriptive approach with interviews, observation, and documentation, the study reveals the institution’s pivotal role in channeling community aspirations, promoting cultural practices, and mediating with the village government. However, limited youth participation and inadequate training hinder effectiveness, while community solidarity and local leadership provide strong support. Novelty: This research delivers a granular, village-level analysis of how traditional institutions navigate modernization pressures while sustaining intangible heritage. Implications: Findings highlight the necessity for targeted youth engagement and capacity-building programs to strengthen traditional institutions as cultural stewards in rural Indonesia. Highlights: Traditional institutions are central to preserving Lung Anai’s Dayak Kenyah cultural heritage. Youth disengagement and lack of training threaten continuity of traditions. Community support and leadership are key enablers for cultural sustainability. Keywords: Cultural Preservation, Traditional Institutions, Youth Engagement, Dayak Kenyah, Lung Anai Village